Induction of prothrombin synthesis by prothrombin fragments. - Graves, C B (1981)
The mechanisms by which blood levels of prothrombin (PT) are regulated in the vitamin K-sufficient state are unknown. We have studied PT synthesis by Reuber H-35 rat hepatoma cells exposed to vitamin K and [3H]leucine in serum-free cultures. Administration to the culture system of exogenous bovine PT and rat PT was characterized by increases in endogenous PT synthesis and secretion of 2- and 3-fold, respectively. This induction required endogenous proteolytic degradation of PT. Studies conducted with bovine PT fragment 1 (residues 1-156) demonstrated up to 5-fold increases in PT synthesis. This induction was dose dependent and saturable. Addition of bovine PT chymotryptic fragments to the cells indicated that the NH2-terminal peptide of prothrombin (residues 1-42) contained the requisite structural elements for the induction. Peptide-bound gamma-carboxyglutamate residues were required for the observed stimulation of PT synthesis. These results suggest that PT synthesis might be regulated physiologically by the products formed during its normal turnover and consumption during blood coagulation.